Clinical and Genetic Characteristics of Chinese Children With GLUT1 Deficiency Syndrome: Case Report and Literature Review - Hu, Qingqing; Shen, Yuechi; Su, Tangfeng; Liu, Yan; Xu, Sanqing (Frontiers in Genetics, 2021)
Objective GLUT1 deficiency syndrome (GLUT1-DS) is a rare, treatable neurometabolic disorder. However, its diagnosis may be challenging due to the various and evolving phenotypes. Here, we report the first Chinese familial cases with genetically confirmed GLUT1-DS, and analyze the characteristics of Chinese children with GLUT1-DS from clinical, laboratory and genetic aspects. Methods We reported a Chinese family with three affected members with GLUT1-DS and searched the relevant articles up to September 2020 from PubMed, WOS, CNKI, and WanFang databases. A total of 30 Chinese patients diagnosed with GLUT1-DS (3 newly identified patients in one family and 27 previously reported ones) were included and analyzed in this study. Results The median age of onset of the 30 patients (male: 18, female: 12) was 8.5 months (range, 33 days to 10 years). Epileptic seizures were found in 25 patients, most with generalized tonic-clonic and focal ones. Movement disorders were in 20 patients - frequently with ataxia and dystonia, developmental delay in 25 patients, and microcephaly only in 6 patients. Cerebrospinal fluid (CSF) analysis showed decreased CSF glucose (median 1.63mmol/L, range 1.1~2.6mmol/L) and glucose ratio of CSF to blood (median 0.340, range 0.215~0.484). The genetic testing performed in 28 patients revealed 27 cases with pathogenic variations of the SLC2A1 gene, including 10 missense, 9 frameshift, 3 nonsense, 3 large fragment deletion and 2 splice-site mutations. Most patients had a good response to the treatment of ketogenic diet or regular diet with increased frequency. Although 3 patients in this Chinese family carried the same pathogenic mutation c.73C>T (p.Q25X) in the SLC2A1 gene, their symptoms and responses to treatment were not exactly the same. Conclusions The clinical manifestations of GLUT1-DS are heterogeneous, even among family members sharing the same mutation. For children with unexplained epileptic seizures, developmental delay and complex movement disorders, it is helpful for the diagnosis of GLUT1-DS by detection of low CSF glucose or SLC2A1 gene mutations. Early initiation of ketogenic diet treatment significantly improves the symptoms and prognosis of GLUT1-DS.